Building web services with microsoft azure : quickly develop scalable, REST-based applications or services and learn how to manage them using Microsoft Azure /: quickly develop scalable, REST-based applications or services and learn how to manage them using Microsoft Azure. (2015) - Belotserkovskiy, Alex; Kaufman, Stephen; Sachdeva, Nikhil
No abstract available